IBM TS7700 R5 DS8000 Object Store user's guide - Brettell, Dave; Fujiwara, Rin; Goodall, Lourie (IBM Redbooks, 2022)
The IBM® TS7700 features a functional enhancement that allows for the TS7700 to act as an object store for transparent cloud tiering with IBM DS8000®, DFSMShsm (HSM), and native DFSMSdss (DSS). This function can be used to move data sets directly from DS8000 to TS7700. This IBM Redpaper publication provides a functional overview of the features, provides client value information, and walks through DFSMS, DS8000, and TS7700 set up steps.